Governing the Algorithm: A Mediation Analysis of Digital Transformation, Bureaucratic Discretion, and Service Quality in a Developing Democracy - Emir Abdullah; Aylin Yermekova; Benyamin Wongso; Ahmad Badruddin (HM Publisher, 2025)
Governments worldwide are implementing digital transformation policies to enhance public service delivery. However, the impact of these algorithm-driven systems on street-level bureaucrats remains critically under-examined. This study investigates the complex pathways through which Indonesia's e-government policy affects bureaucratic work and service outcomes. This study employed a mixed-methods explanatory sequential design. Quantitative data were collected from 500 public officials across five Indonesian provinces. An E-Government Implementation Index (EGII) was constructed. We used Ordinary Least Squares (OLS) regression and a formal mediation analysis with bootstrapping to analyze the relationships between EGII, Perceived Bureaucratic Discretion (PBD), and Bureaucrat-Perceived Public Service Quality (B-PSQ). This was supplemented by 20 in-depth, semi-structured interviews to explain the statistical findings. Regression analysis confirmed a significant negative association between EGII and PBD (β = -0.47, p < 0.001) and a significant positive association between EGII and B-PSQ (β = 0.62, p < 0.001). The mediation analysis revealed that EGII has a strong, positive direct effect on B-PSQ (Effect = 0.57, p < 0.001) and a small but significant negative indirect effect through the reduction of PBD (Effect = -0.05, p < 0.01). Qualitative data revealed that officials feel constrained by